Analisis dan Evaluasi Pengaruh Temperatur, Pencahayaan dan Kebisingan terhadap Jumlah Produksi pada Fabrikasi Ekstrusi Alumunium dengan Menggunakan Metode Sugeno dalam Logika Fuzzy - Sepriandi Parningotan; Tri Mulyanto (Politeknik Manufaktur Negeri Bangka Belitung, 2020)
The concept of ergonomics in the work environment is an important to be applied in an industry. The application of ergonomics is expected to create a safe, healthy and comfortable work environment so that work becomes more productive and efficient and there is a guarantee of work quality. Based on the problems that occur, a method is needed to overcome fluctuations in the amount of production, one of the ways is by using fuzzy logic. The conclusion of this paper is the analysis and processing of data carried out using the Sugeno method, both software and manual by entering the temperature input variable of 31o C, lighting of 500 lux and noise 85 db, the results obtained for the amount of production in the next period of 531 in the manual calculation , while the software count is 487. Based on these results the number of manual calculations and Matlab software with fuzzy logic using the Sugeno method has a difference that is not far from the data received by 281. This means that the percentage of matching fuzzy logic processing with received data is 97.76% .